2016
DOI: 10.1039/c6dt00189k
|View full text |Cite
|
Sign up to set email alerts
|

Defect engineering of UiO-66 for CO2 and H2O uptake – a combined experimental and simulation study

Abstract: Defect concentrations and their compensating groups have been systematically tuned within UiO-66 frameworks by using modified microwave-assisted solvothermal methods. Both of these factors have a pronounced effect on CO2 and H2O adsorption at low and high pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
170
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(196 citation statements)
references
References 44 publications
16
170
0
Order By: Relevance
“…Pore size distribution analysis clearly shows disappearance of pores having half width of 7.4 ,a ssociated with missing cluster defects and well visible in FA_mod (Figure 3b). [17] 1 HNMR analysis of hydrolysed FA_mod-PSE-50 confirms that no exchange of BDC has occurred and all the exchanged PyDC has replaced FA at missing-cluster defective sites,inline with the result of the in situ experiment. This is good evidence that no significant diffusion limitations exist and exchange occurs homogeneously throughout the crystallites (see at the Supporting Information for ad etailed discussion of microstructural aspects of PSE).…”
supporting
confidence: 63%
“…Pore size distribution analysis clearly shows disappearance of pores having half width of 7.4 ,a ssociated with missing cluster defects and well visible in FA_mod (Figure 3b). [17] 1 HNMR analysis of hydrolysed FA_mod-PSE-50 confirms that no exchange of BDC has occurred and all the exchanged PyDC has replaced FA at missing-cluster defective sites,inline with the result of the in situ experiment. This is good evidence that no significant diffusion limitations exist and exchange occurs homogeneously throughout the crystallites (see at the Supporting Information for ad etailed discussion of microstructural aspects of PSE).…”
supporting
confidence: 63%
“…The low separation factor might be caused by the missing linkers generated by the addition of acetic acid in the solvothermal synthesis. Indeed, the water adsorption increased as the number of missing linkers increased , . Thus, the ethanol selectivity of UiO‐66 could be improved by preparing the membrane with less missing linkers.…”
Section: Resultsmentioning
confidence: 99%
“…44,45 Recently, Goodwin and co-workers showed that correlations between defects can be introduced and controlled, yielding nanoscale defect structures. 46 The presence of these defects may alter the catalytic properties, 47,48 thermal stability, 49 proton conductivity, 50,51 and adsorption behavior 43,5255 of the host material. While recent work also indicates a decrease in bulk modulus and hence robustness upon the introduction of defects, 54,56 it remains to be investigated how the precise molecular nature of these defects alters the pressure-induced disorder in UiO-66-type materials.…”
Section: Introductionmentioning
confidence: 99%